Amir Khan: A Boy From Bolton: My Story - Khan, Amir and Garside, Kevin (Bloomsbury Publishing Plc, 2006)
A Boy from Bolton, Amir's autobiography, will tell the story of a boy who Don King has compared to Sugar Ray Robinson, but who still lives at his mum and dad's semi-detached in Bolton with his sister and two kid brothers. A boy who fasts in the Islamic holy month of Ramadan, even when he has a major fight the next day, and can sometimes be spotted helping out on the till at Moods Fast Food, his uncle and auntie's curry house in Bolton, if they're having a busy night ...
Keywords: Amir Khan; Biographies & Autobiographies; Non-Fiction